Hypoxia enhances indoleamine 2,3-dioxygenase production in dendritic cells - Song, Xiang (Oncotarget, 2018)
Hypoxia-associated metabolic reprogramming modulates the biological functions of many immune and non-immune cells, and affects immune response types and intensities. Adenosine and indoleamine 2,3-dioxygenase (IDO) are known immunosuppressors, and adenosine is a hypoxia-associated product. We investigated the impact of hypoxia on IDO production in dendritic cells (DCs). We found that hypoxia (1% O(2)) enhances IDO production in DCs, and this increase was dependent on the adenosine A3 receptor (A3R), but not A2aR or A2bR. A3R blockade during hypoxia inhibited IDO production in DCs, while A2bR blockade further enhanced IDO production. Activating A2aR had no effect on IDO production. Hypoxia (1% O(2)) upregulated CD86, CD274, HLA-DR, and CD54, and downregulated CD40 and CD83 in DCs as compared to normoxia (21% O(2)). IDO inhibition in hypoxia-conditioned DCs reversed MHC-II, CD86, CD54, and CD274 upregulation, but further downregulated CD40 and CD83. Our findings offer guidance for pharmacological administration of adenosine receptor agonists or antagonists with the goal of achieving immune tolerance or controlling insulin resistance and other metabolic disorders via IDO modulation.